Graffiti : paisagem urbana marginal. A inserção do graffiti na paisagem urbana de Vitória (ES) - Bissoli, Daniela Coutinho (2011)
This dissertation takes as its subject one of the most characteristic art forms on the contemporary urban landscape: graffiti. The topic in question deals as much with the depiction of daily urban life in the age of antiquity as the subversive actions of